Gerard Cohen-Vrignaud, Radical Orientalism: Rights, Reform, and Romanticism. Cambridge: Cambridge University Press, 2015. 268 pp. ISBN: 9781107110328, £64.99. Issue 22 (2016) - Aparicio, Valentina P.
No abstract available